Participation of Women Farmers Group Members to Sustainable Food House Area Program (Case Study of Tamalanrea District, Makassar City, South Sulawesi Province) - Fitri Anugrah Sari; Mahyuddin Mahyuddin; Heliawaty Heliawaty (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
Makassar City has implemented the KRPL (Sustainable Food House Area) Program as a flagship program as an effort to develop and fulfill food needs in Makassar. The Makassar City Government itself has started from 2017 to 2019 by developing in 15 sub-districts in Makassar City. In the Tamalanrea sub-district itself, there are 4 groups of women farmers who are implementing the KRPL program both in the growth and development period. In implementing the program, the community is an important element in which motivation plays an important role for the sustainability of the program. The purpose of this research is to determine the level of participation members women's farmer groups. The data analysis method used is descriptive quantitative, namely the research method used to analyze data in the form of numbers by describing or describing the collected data as they are. To determine the level of participation of members women's farmer group used score analysis and will be classified into categories based on the score interval. The results of this research conclude that the participation rate of members of the Women Farmers Group, Tamalanrea District, Makassar City is in the medium category with an average total score of 40.54 with persentage 67.57%